Numerical Simulation of Split-Hopkinson Pressure Bar Tests for the Combined Coal-Rock by Using the Holmquist–Johnson–Cook Model and Case Analysis of Outburst - Beijing Xie; Dongxin Chen; Hao Ding; Guangyu Wang; Zheng Yan (Advances in Civil Engineering)
In the coal and rock dynamic disasters, such as the rock burst, dynamic load damage often acts simultaneously on the combined coal and rock mass. Based on the split-Hopkinson pressure bar (SHPB) test of the combined coal and rock with a bullet velocity of 4.590–8.791 m/s, the numerical model of four kinds of combined coal and rock with different sandstone-coal-sandstone ratios, including 1 : 1 : 1, 2 : 1 : 1, 1 : 1 : 2, and 1 : 2 : 1, is investigated. A finite element software (LS-DYNA) and the Holmquist–Johnson–Cook (HJC) constitutive model of rock are employed in these regards. The stress waveform, the oscillation phenomenon of stress wave, and the damage process of the specimen in the impact test of the composite coal and rock are studied. The obtained results show that the compression-shear failure is the main failure mode of the coal body and the tensile failure of the sandstone along the axial direction in the composite coal-rock specimens. Moreover, it is found that combination of coal and rock samples is mainly destroyed by the coal body, which has no correlation with the impact speed and combination mode. Finally, numerical simulation about Hongling coalmine extralarge tunnel malfunction is carried out. Obtained results showed the protruding and stress change processes of the coal seam of the tunnel exposing. It is found that the simulation results are in an excellent agreement with those from the field investigation. The present study may provide a reference for further understanding the mechanism of the coal and rock dynamic disasters, such as the rock burst.